Correlations between lung pneumonic lesions and serologic status for key respiratory pathogens in slaughtered pigs in northern Uganda - Oba, Peter; Dione, Michel M.; Wieland, Barbara; Mwiine, Frank N.; Erume, Joseph (Porcine health management, 2021)
A cross-sectional study of slaughtered pigs was conducted in Lira district, Uganda, to (1) determine the prevalence and severity of pneumonia and (2) establish relationships between pneumonia types and the serological status for key respiratory pathogens. Using enzyme-linked immunosorbent assays (ELISAs), sera were screened for antibodies against Mycoplasma hyopneumoniae (M. hyo), Actinobacillus pleuropneumoniae (App), porcine reproductive and respiratory syndrome virus (PRRSv) and porcine circovirus type 2 (PCV2). Postmortem, lungs were grossly scored for pneumonia types and pneumonic lesions. Pneumonia types were characterized as catarrhal purulent bronchopneumonia (CPBP), pleuropneumonia (PLP) and pleuritis. The percent of lung surface affected by pneumonia was determined by estimating the affected surface area of each lung lobe. Each lobe was assigned scores based on the approximate volume represented and the total percentage of lung surface affected obtained as a sum of individual lobe scores. Metastrongylus spp. helminth infection was determined by examining lungs for gross presence or absence. RStudio was used for data analysis and presentation. Wilcoxon rank sum tests were used to compare median pneumonia lesion scores and serostatus for each studied pathogen. An ordinal logistic regression model was fitted to evaluate the odds of multiple pneumonia, with pathogen serostatus and Metastrongylus spp. infection as predictors. Results: One hundred sixty-seven (n = 167) lungs were examined for pneumonic lesions. The prevalences of CPBP, PLP and pleuritis were 29.9% (95% CI 22.9–36.9), 74.2% (95% CI 67.5–80.9) and 17.3% (95% CI 22.4–36.3), respectively. The true prevalence of PCV2 was 9.7% (95% CI 4.5–16.8), that of PRRSv was 7.5% (95% CI 2.7–14.2), that of M. hyo was 11.5% (95% CI 7.2–18.0), that of App was 25.1% (95% CI 18.5–38.0), and that of Metastrongylus spp. was 29.3% (95% CI 22.9–36.6). The odds of multiple pneumonia forms increased in pigs with multiple pathogens (ORs 2.6, p = 0.01) and Metastrongylus spp. infestation (OR 2.5, p = 0.003), suggesting synergistic effects of coinfections in the induction of lesions. Conclusions: This study revealed a high prevalence and severity of pneumonic lesions in slaughtered pigs. It provides baseline information and evidence for the magnitude of pneumonia associated with the studied pathogens and justifies future studies on their potential economic impacts on Ugandan pigs.
Keywords: Lira; Lesion scores; Lungs; Respiratory; Pigs; Pneumonia; Porcine; Uganda